2015
DOI: 10.3389/fnana.2015.00082
|View full text |Cite
|
Sign up to set email alerts
|

Cortical signature of patients with HBV-related cirrhosis without overt hepatic encephalopathy: a morphometric analysis

Abstract: Previous studies have shown that patients with hepatitis B virus-related cirrhosis (HBV-RC) without overt hepatic encephalopathy (OHE) are associated with a varying degree of cognitive dysfunction. Several resting-state functional magnetic resonance imaging (fMRI) studies have been conducted to explore the neural correlates of such cognitive deficits, whereas little effort has been made to investigate the cortical integrity in cirrhotic patients without OHE. Here, using cortical thickness, surface area and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
4
8
0
Order By: Relevance
“…In particular in the occipital lobe, Region 12R (right lingual) and 20R (right peri calcarine) in Figure 12 seem to be the most affected regions related to visuospatial processing since they have more connections with differences between the two groups. This agrees with the findings that damage to the lingual gyrus leads to a form of topographic disorientation (Kravitz et al, 2011) and abnormalities in calcarine sulcus, which is a key node of the ventral visual pathway, are related to impaired visual information processing (Wu et al, 2015).…”
Section: 5supporting
confidence: 92%
“…In particular in the occipital lobe, Region 12R (right lingual) and 20R (right peri calcarine) in Figure 12 seem to be the most affected regions related to visuospatial processing since they have more connections with differences between the two groups. This agrees with the findings that damage to the lingual gyrus leads to a form of topographic disorientation (Kravitz et al, 2011) and abnormalities in calcarine sulcus, which is a key node of the ventral visual pathway, are related to impaired visual information processing (Wu et al, 2015).…”
Section: 5supporting
confidence: 92%
“…The lateral occipital cortex plays a key role in visual object processing 32 , and this region was significantly activated by attention 33 and during object-based selection in previous functional MRI (fMRI) studies 34 . Previous studies have also shown that significantly increased local gyrification index in the lateral occipital cortex and the mean cortical thickness of the regions with structural abnormalities were negatively correlated with the PHES of patients with hepatitis B virus-related cirrhosis without overt HE 35 . In addition, judgement-related blood oxygenation level-dependent (BOLD) activation was decreased in CHE compared to controls in the right inferior parietal cortex (IPL).…”
Section: Discussionmentioning
confidence: 79%
“…Similarly, the corticocortical projections from the precuneus to the lateral parietal areas and premotor cortex 42 play a pivotal role in the motor coordination with visual guidance of hand movements 43 and reaching 44 . Prior structural fMRI studies have identified significantly increased cortical thickness in the precuneus in HBV-related cirrhotics, suggesting low-grade brain edema in this region that potentially contributes to the impaired connectivity in the precuneus 35 . These findings are consistent with several studies showing decreased regional homogeneity in the precuneus and changes of amplitude of low frequency fluctuation and fraction in CHE patients 45,46 .…”
Section: Discussionmentioning
confidence: 96%
“…In agreement with this result, previous studies also revealed similar enlargements in these specific GM regions in cirrhotic patients. For example, cirrhotic patients with cognitive impairment have demonstrated a significant increase in cortical thickness in the bilateral lingual and parahippocampal gyrus, right posterior cingulate cortex, precuneus, peri-calcarine sulcus, and the fusiform gyrus 47 . In addition, cirrhosis is often accompanied by an increase in thalamic volume 19,42,48 , so much so that increased GMV in the thalamus has been regarded as an additional characteristic of MHE.…”
Section: Discussionmentioning
confidence: 99%
“…(2020) 10:2490 | https://doi.org/10.1038/s41598-020-59433-1 www.nature.com/scientificreports www.nature.com/scientificreports/ It is important to note that the mechanisms underlying increased GMV in MHE are not well understood. One possible reason may be the diffuse, low-grade, cerebral edema related to Alzheimer's type II astrocytes during chronic liver disease 47,49 . The existence of both decreases and increases in GMV in MHE may reflect brain structural reorganization due to chronic liver failure.…”
Section: Scientific Reports |mentioning
confidence: 99%